(untitled) (Revista Puertorriqueña de Psicologia, 2016)
The purpose of this study is explore the image that a group of administrators have of the industrial organizational psychologists. The study was based on a questionnaire that was developed by the research team and administered individually to the subjects. The study findings replicate those found on previous cross-cultural studies. The sample organizations use the services of the industrial organizational psychologists in the traditional areas of training, development of personnel selection procedures, seminars and conflict resolution. Even though the use made of these pscyhological services is limited, 65% of the participants expressed the desirability of contracting for these services in the future.